Evaluating University Degree Programs Regarding the Effective Use of Public and Private Funding - Douglas Burleigh; Marina Kuimova; Maxim Mazhanov (International Review of Management and Marketing, 2017)
The subject of this paper is making educated decisions on the use of Public (governmental) and private funding to support the acquisition of university degrees in majors that have a low probability of providing a career or employment. Discussion topics include return on investment, and the realistic expectations of obtaining jobs in the field of study after graduation. This paper discusses the effectiveness of university degree programs with respect to the use of public funding and the probability of graduates’ employment. It is proposed that a system of metrics be developed to evaluate the potential of each degree program to provide employment in that field and to predict the probability of employment.